If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(13b-6)-4(3b+4)=-2
We move all terms to the left:
(13b-6)-4(3b+4)-(-2)=0
We add all the numbers together, and all the variables
(13b-6)-4(3b+4)+2=0
We multiply parentheses
(13b-6)-12b-16+2=0
We get rid of parentheses
13b-12b-6-16+2=0
We add all the numbers together, and all the variables
b-20=0
We move all terms containing b to the left, all other terms to the right
b=20
| 63x^2+12x-3=0 | | --8y=-22 | | 3g+4/7=1 | | (X+1)(x+1)46=0 | | 2x-8x-15=6x+2-15 | | 13-n=21 | | (y/2)^2=49 | | H(t)=-2t^2+10t+1 | | 6x+5=-51-8 | | 2(3k-1)=24 | | 6x+5=51-8x | | 22=2+-13t | | y/9+3y=27 | | 5a-12=7a+ | | 3/2b+5=20−b | | 5a12=7a+2 | | 5^3x=4^x+3 | | 0.05y+0.02(6000y)=270 | | 234x-94-108=788 | | 2^(x^2+2x-45)=64^(9/2) | | 5x2x²=6x | | 4(5x-3)=21x= | | 9(14x+9)-8(13+10)-21x-1=55 | | 9(4c-1)-18=34c+9= | | 2-5x=18+3x= | | 60=2w^-14w | | 3x-2x²=6x | | 3(x+7)=(28)24 | | 2x+11x+x=127 | | 2(7.4r-7.9)=44.3 | | 5(x-3)-4=3(x+4)-31 | | (x4)²+8=0 |